1999
DOI: 10.1034/j.1399-6576.1999.430312.x
|View full text |Cite
|
Sign up to set email alerts
|

Irrigating fluid absorption during percutaneous nephrolithotripsy

Abstract: Retroperitoneal extravasation can be identified by using ethanol monitoring during and after PNL. Afflicted patients require considerably longer hospitalisation, probably because of the additional injury to surrounding organ structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Symptoms of fluid overload depend on volume of absorption and hemodynamic status. [9] It may lead to neurological or hemodynamic instability. Vascular problems may include bradycardia, hypertension, hypotension and decreased urine output.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of fluid overload depend on volume of absorption and hemodynamic status. [9] It may lead to neurological or hemodynamic instability. Vascular problems may include bradycardia, hypertension, hypotension and decreased urine output.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] However, some studies have reported hyponatremia and hypokalemia and explained these changes by renal tubular dysfunction due to mechanical irritation of kidneys and glycine 1.5% induced hyponatremia during PCNL. 2,[12][13][14] In our study, we compared the change in the two clinically most important electrolytes -sodium (Na) and potassium (K). Difference in serum sodium levels of both the groups was statistically non-significant at all the stages of procedure.…”
Section: Side Effectsmentioning
confidence: 99%
“…Percutaneous nephrolithotripsy (PCNL) is a common technique to treat kidney stones and is also used to fragment and remove the calyx and pelvic stones (1)(2)(3)(4)(5). Nowadays to manage large stones, stones resistant to fragmentation, or stones with an abnormal anatomy in kidney, PCNL is preferred (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…There was no rolled tower on the flank and no change in leg position in csPCNL. This endoscopic technique (csPCNL)which needs continuous irrigation can result in serious complications (5). One of the most important complications is extravasationof large amount of irrigation fluid to retroperitonealspace that increases the likelihood of septic complications (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation